Metacognitive skill assessment model through the blended learning management system in vocational education - Ridwan Daud Mahande; Fitrah Asma Darmawan; Jasruddin Daud Malago (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2021)
This study aims to develop an assessment rubric and produce a metacognitive skill model through the Blended Learning Management System (BLEMS) in project-based learning in vocational education. This study uses the Research and Development (R&D) model of Borg and Gall (1983). The research subjects consisted of two experts (validity), ten students (small group), and 35 students (expanded) from the Faculty of Engineering, Universitas Negeri Makassar, Indonesia. Data were collected using questionnaires and tests: developed assessment instruments and rubrics with three main aspects, planning, monitoring, and evaluation. Conducted assessment tests through self, peer, and teacher assessments. Then analyzed the results of the Assessments with descriptive statistics. The results showed that the Rubric and metacognitive assessment model through BLEMS for vocational education met the validity, practicality, and effectiveness. The integration of metacognitive skill elements: planning, monitoring, and evaluation with self-assessment, peer assessment, and teacher assessment can be an assessment method to measure students' metacognitive thinking skills in project-based learning in vocational education.